Flexural and Surface Properties of PMMA Denture Base Material Modified with Thymoquinone as an Antifungal Agent. Issue 3 (4th September 2018) - Gad, Mohammed M.; Al‐Thobity, Ahmad M.; Fouda, Shaimaa M.; Näpänkangas, Ritva; Raustia, Aune
Abstract: Purpose: To evaluate the effect of addition of different concentrations of thymoquinone (TQ) on the flexural strength, elastic modulus, surface roughness, and hardness of PMMA denture base material. Materials and Methods: A total of 160 rectangular specimens were prepared from heat‐polymerized acrylic resin, with dimensions of 65 × 10 × 2.5 mm 3 for flexural strength testing and 10 × 20 × 3 mm 3 for surface property testing. The specimens were divided into eight groups of 20 specimens: one control group without addition of TQ and seven test groups prepared by adding TQ to acrylic powder in concentrations of 0.5, 1, 1.5, 2, 2.5, 3, and 5 wt%. The polymer was added to the monomer before being mixed, packed, and processed using the conventional water bath method. A universal testing machine was used to measure flexural strength and elastic modulus. A profilometer and a Vickers hardness tester were used to measure surface roughness and hardness, respectively. One‐way ANOVA and the Tukey‐Kramer multiple‐comparison test were used for statistical analysis, with statistical significance at p ≤ 0.05. Results: Addition of TQ to PMMA denture base material significantly decreased flexural strength and elastic modulus at high concentrations ( p < 0.01), while no significant differences were observed at low concentrations (0.5%, 1% TQ) in comparison with the control group. At high TQ concentrations, surface roughness increased while hardness decreased ( p < 0.0001), and no significant differences were observed at low concentrations (0.5%, 1% TQ) in comparison with the control group. The most favorable addition values were 0.5% and 1% TQ in all TQ groups. Conclusions: Addition of TQ did not affect the flexural and surface properties of PMMA denture base material at low concentrations (0.5%, 1% TQ) and could be incorporated into PMMA denture base material as an antifungal agent.